Risky sexual behaviors and their associated factors within high school students from Collège Saint André in Kigali, Rwanda: An institution-based cross-sectional study - Ndagijimana, Emmanuel; Biracyaza, Emmanuel; Nzayirambaho, Manasse (Frontiers in Reproductive Health, 2023)
Background: Risk sexual behaviors (RSB) remain public health concerns in adolescents from Sub-Sahara Africa and these practices may increase vulnerability to reproductive health problems, while no early healthcare strategies are taken. While previous studies reported that adolescents are engaged in these RSB due to diverse influences such as teenage stage, urbanization and change of the environment they experience, there is a dearth of studies on RSB among the adolescents in SSA. This study assessed the magnitude of RSB and the factors associated among in-school adolescents. Methods: School-based cross-sectional study was conducted among 263 from Saint Andre school students in Kigali, Rwanda from 03 July 2020 to September 30, 2020. Systematic random sampling techniques were employed. All data were entered into Epi-Data and analyzed using SPSS version 25. Chi-square test and multivariable logistic regression analysis were applied to determine factors associated with risk sexual behaviors. Confidence intervals of 95% and 5% for statistical significance were maintained. Results: Of 263 participants, 109 (41%) experienced RSB in lifetime. Among them, 66 respondents (60.55%) utilized contraceptives methods to prevent sexually and reproductive problems that are the results of unprotected sexual intercourses. Experienced domestic violence increased the odds to experience RSB (OR=4.22; 95%CI: 1.6-11.23) than their counterparts. Those who were in grade 11 (OR=2.68; 95%: 1.06-6.78) and grade 12 (OR=4.39; 95%CI: 1.82-10.56) were more likely to practice risk RSB than those from grade 10. Alcohol users were almost more likely to experience RSB (OR=3.9; 95%CI: 1.97-5.5) than their counterparts. Those who lived away from their biological parents had higher likelihoods to experience RSB (OR=2.5; 95%CI:1.14-4.42) than those who lived with one or both parents. Students who experienced peer pressure were more likely engaged in RSB (OR=3.9; 95%CI: 2.01-7.51) compared to their counterparts. Conclusion: Promoting specific interventions programs built upon the factors associated with RSB among the high school students needs to be prioritized.